Raised Arterial Pressure and Microalbuminuria in Type 2 Diabetic Subjects with Familial Hypertension - Rahman, Md Anisur; Billah, Md Mostarshid; Mitra, Palash; Hossan, Md Emtiaz; Hossain, Md Jakir; Haque, Wasim Md Mohosin Ul; Mansur, Md Abul (Bangladesh Critical Care Journal, 2016)
Background and Aims : Microalbuminuria is claimed to be an early marker of nephropathy in type 2 diabetes.The raised arterial pressure is an important factor in the progression of diabetic nephropathy. There is a significant correlation between blood pressure and the progression of albuminuria in both type 1 and type 2 diabetes. This study in Bangladeshi type 2 diabetic patients was to evaluate whether microalbuminuria and raised arterial pressure are influenced by familial predisposition to hypertension. Methods : Sixty three newly diagnosed Bangladeshi type 2 diabetic patients were investigated. The diabetic subjects were divided into two groups as diabetes with family history of hypertension (n=37) and diabetes without family history of hypertension (n=26). Diabetic subjects were further divided into normotensive (n= 46) and hypertensive (n= 17); diabetic normoalbuminuric (n 44) and diabetic microalbuminuric (n 19) subgroups. Serum glucose was measured by glucose-oxidase; blood urea, serum creatinine and urinary creatinine by enzymatic-colorimetric method and urinary albumin by immunoturbidimetry method. Results : systolic blood pressure (SBP), diastolic blood pressure (DBP) and microalbuminuria were significantly elevated in diabetic subjects with familial predisposition to hypertension when compared to diabetic subjects without familial predisposition to hypertension [SBP (127±16 vs 110±14) mmHg P= 0.001; DBP (81±9 vs 72±11) mmHg P= 0.001; Microalbuminuria 2.23(0.28-9.43) vs 1.52(.29-3.91) mg/mmol p<0.03]. When diabetic normotensive subjects were compared with diabetic hypertensive subjects for microalbuminuria, no significant difference was found among themselves [median (range) 1.67(0.17-8.62) vs 1.70(.28-9.43) mg/mmol p = NS]. Comparison of blood pressure was found no significant difference between diabetic normoalbuminuric and diabetic microalbuminuric subjects [systolic blood pressure (117±17 vs 125±17) mmHg p= NS ; diastolic blood pressure (76±11 vs 82±10) mmHg p= NS ]. Conclusion : Microalbuminuria, a marker of early diabetic nephropathy and raised arterial pressure, a progression factor of nephropathy are more influenced by familial predisposition to hypertension in diabetic population irrespective of presence or absence of microalbuminuria and hypertension. Bangladesh Crit Care J March 2016; 4 (1): 14-18